Assessment of the accuracy of reproduction of the lower limb axis using an individual instrument during endoprosthetics with kinematic alignment of the knee joint - Golovakha, Maksym; Bondarenko, Stanislav (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2025)
Objective. To assess the accuracy of reproduction of the kinematic axis of the lower limb using an individual instrument during total knee arthroplasty (TKA) by comparative radiographic analysis before and after surgery. Methods. Using radiographic analysis, an analysis of the knee arthroplasty of 10 patients operated on using an individual instrument was performed, the kinematic axis was restored (3 men and 7 women). The age range was from 56 to 71 years. Before surgery, patients underwent computed tomography of the lower limbs, and after it, radiography with vertical positioning of the feet. The individual instrument was manufactured using the original method. Results. A comprehensive assessment of the accuracy of reproduction of spatial landmarks of the lower limb during TKA was carried out using an individual surgical instrument developed on the basis of computed tomography and the principles of kinematic alignment. Analysis of deviations of the proximal medial tibial angle in the postoperative period revealed a mean absolute error of 0.15°, with a mean relative error of 0.74 %. At the same time, for the distal lateral femoral angle, an absolute error of 0.24° and a relative error of 0.27 % were established. Preoperatively, the mean value of the planned axis was 88.71°, postoperatively — 86.58°, which corresponds to a mean varus deviation of 2.15° and a relative error of 2.47 %. At the same time, it was found that the technical axis indicators were 88.55° before surgery and 86.67° after, respectively, with a mean varus deviation of 1.88° and a relative error of 2.28 %. Conclusion. A custom instrument allows for accurate reproduction of the kinematic axis of the lower limb, which can be crucial for achieving functional outcome and patient satisfaction.